Rapidly Growing and Asymptomatic Skull Base Lesion. Issue 2 (March 2019) - Tolisano, Anthony M.; Lin, Kevin; Hunter, Jacob B.
Abstract : Abstract: Trochlear schwannomas typically present with diplopia and are extremely rare benign intracranial neoplasms that require the combined expertise of neurotologists and neurosurgeons for surgical excision. A combined petrosal approach offers a surgical route for removal of growing and/or symptomatic tumors. A study of a trochlear nerve schwannoma that demonstrated rapid growth but was otherwise asymptomatic was presented in this study.